ANALYSIS OF INCREMENTAL INNOVATION AND RADICAL INNOVATION ON THE COMPETITIVE ADVANTAGE OF LAMPIT PRODUCT MSMES IN THE WETLAND AREA OF HULU SUNGAI UTARA REGENCY - M. Hasanur Arifin; Rasyidi Rasyidi; Jainab Jainab; Paulia Paulia; Pahrurazi Pahrurazi (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
The performance of MSMEs of HSU lampit products began to decline due to the lack of innovation from the MSMEs of the lampit products themselves. Every MSME must be ready to make changes by innovating because MSMEs will be complicated to compete with their competitors if there is no innovation. MSMEs are required to constantly innovate in today's increasingly modern era. Competition is something that must be faced by a business unit. The objectives of this study are (1) Analyzing incremental innovations on the competitive advantage of LAMPIT product MSMEs in the wetland area of Hulu Sungai Utara Regency, (2) Analyzing radical innovations toward the competitive advantage of LAMPIT product MSMEs in the wetland area of Hulu Sungai Utara Regency. The research method using the research approach used is a quantitative approach. The data collected through the questionnaire was then analyzed using the PLS (Partial Least Square) analysis model using the help of SmartPLS software version 3. The result of this study is that incremental innovations and radical innovations have a significant effect on the competitive advantage of Lampit Product MSMEs in the wetland area of Hulu Sungai Utara Regency.